Does central fatigue limit muscle force generation capacity during fatigue? - Puleo, A.; Contessa, P. (ISBS Proceedings Archive (Michigan), 2017)
There is general agreement on peripheral factors of muscle fatigue that develop within the muscle and impair muscle fiber contractile mechanisms and muscle performance. Central factors of muscle fatigue that arise within the central nervous system have also been suggested to influence muscle force during fatigue. However, no direct empirical evidence of their influence on muscle force capacity has yet been reported. We used a force model to investigate whether peripheral factors are sufficient to explain the loss of muscle force generation capacity during fatiguing submaximal voluntary contractions that is commonly attributed to central factors. Our simulations showed that the force behavior during fatigue could be explained solely by peripheral factors. These data raise concerns about the influence of central factors on muscle force generation capacity during fatigue.